Testing of laser ablation ion source for JYFLTRAP - Poleshchuk, Kateryna (2015)
In this work, we have constructed and tested a laser ablation ion source for JYFLTRAP Penning trap at the IGISOL (Ion Guide Isotope Separator On-line) facility. The calibration of the Penning trap parameters requires reference ions or ion clusters that have well-known masses with relatively small mass uncertainty. These ions and ion clusters can be created with certain solid targets, which contain large amounts of isotopes of reference masses and by using a laser for target ablation. In this work simulations of ion source parameters, construction, testing and improving a laser ablation ion source setup have been done. Targets with relatively large abundances of 63Cu and 65Cu, 85Rb, 87Rb, 115In, 120Sn have been used for the laser ablation. Some of these ions were successfully created and measured with the Penning trap.